(untitled) (TANMIYAT AL-RAFIDAIN, 2025)
Amid the rapid global digital transformation, Human Resource Technology (HRT) has emerged as a fundamental pillar of organizational development and the achievement of strategic goals. Job enrichment is considered a vital concept in the modern work environment, closely linked to employee satisfaction, motivation, productivity, and retention. Accordingly, this study aims to explore the perceptions of administrative employees at Najran University regarding the impact of HRT on enhancing job enrichment. The research problem is that, despite the growing adoption of HRT in institutions, its effect on job enrichment remains unclear, raising questions about its contribution to improving job quality, satisfaction, and employee motivation. The study seeks to determine the impact of HRT on promoting job enrichment among administrative staff at Najran University. A comprehensive descriptive survey methodology was employed, suitable for the study’s objectives. The findings revealed that the dimensions of HRT—namely data management, internal communication and collaboration, and compliance and risk management—play a significant role in enhancing the diversity of employee skills, reflecting their capacity to support professional development and broaden functional competencies. In contrast, the dimension of employee experience management showed no statistically significant impact on skill diversity, suggesting weaknesses in its mechanisms or a lack of direct relevance to skill development. The study recommends strengthening the use of data management and internal communication technologies at the university, given their clear impact on supporting performance autonomy by providing accurate information, facilitating access, and improving communication channels between employees and departments. It also recommends leveraging data management tools to enhance feedback processes by regularly collecting and analyzing employee input, thereby improving the quality and effectiveness of feedback within the organization.